The Effect Of Company Size On Capital Structure In Tourism, Restaurant, And Hotel Companies Listed On The Indonesia Stock Exchange In 2019-2020 - Iwan Budiherwanto (Universitas Sains dan Teknologi Komputer, 2021)
This research on profitability aims to examine the effect of firm size on capital structure. The population in this research are tourism, restaurant, and hotel companies listed on the Indonesia Stock Exchange in 2019 - 2020. The sample in this research was selected through purposive sampling, so that a sample of 31 companies was obtained. The statistical test tool uses multiple regression analysis. Capital ctructure in this research was measured using Debt to Equity Ratio, while firm size was measured using total assets. The results show that firm size has negative and insignificant effect on capital structure. The size of the company has no effect on management decisions to manage capital structure, whether management will use accounts payable or use its own capital. The bigger the company, the management will decide to manage using their own capital. There is a possibility that the larger the size of the tourism, restaurant, and hotel companies, management will tend to use capital originating from within the company, especially to reduce risk. This is exacerbated by the COVID-19 pandemic which has caused a sluggish tourism worldwide. Investors may withdraw their money in tourism and divert their funds to other fields that are considered more profitable.